Abundance, fecundity and morphometrics of freshwater crab, Potamon sp. of the Padma river (University Journal of Zoology, Rajshahi University, 2007)
Key words: Dohar; Potamon sp., fecundity; gravid; adult crab; breeding season Univ. j. zool. Rajshahi Univ. Vol.24, 2005. pp. 35-38